P16 Protein and Human Papillomavirus (HPV16, 18) Expressions in Oral Lichen Planus and Squamous Cell Carcinoma - Suhaib R Muhsin; Ahlam H Majeed (College of Dentistry/ University of Baghdad, 2015)
Background: Oral carcinogenesis is a molecular and histological multistage process featuring genetic and phenotypic markers for each stage, which involves enhanced function of several oncogenes and/or the deactivation of tumor suppressor genes, resulting in the loss of cell cycle checkpoints. The progression towards malignancy includes sequential histopathological alterations ranging from hyperplasia through dysplasia to carcinoma in situ and invasive carcinoma. The p16 gene produces p16 protein, which in turn inhibits phosphorylation of retinoblastoma, p16 play a significant role in early carcinogenesis. Human papillomavirus is a well established heterogeneous virus and plays an important role in oral cancers. The aims of the study were to evaluate, compare and correlate the immunohistochemical expression of p16 protein and HPV16/18 with each other in oral lichen planus and oral squamous cell carcinoma, and with various clinicopathological findings. Materials and methods: fourty formalin-fixed, paraffin embedded tissue blocks (24 cases of oral lichen planus, and 16 cases of oral squamous cell carcinoma) were included in this study, an immunohistochemical staining was performed using anti p16 monoclonal antibody, and anti HPV16/18 monoclonal antibodies. Results: Positive IHC expression of p16 was found in 11 cases (68.75%) of OSCC, and in 19 cases (79.166%) of OLP. Positive IHC expression of HPV16 was found in 2 cases (12.5%) of OSCC,and in 1 case (4.16%) of OLP. IHC expression of HPV18 showed negative expression in all cases of OSCC,and found only in 1 case (4.16%) of OLP. Conclusions: This study signifies the statistically non significant correlation between p16 and HPV 16/18 in OLP and OSCC.